تأثير مدة ترك الخياطة على النجاح طويل الأمد لعملية إعادة تموضع الشفة - يوسف, تهامة (Latakia University Journal -Medical Sciences Series, 2018)
تعتبر عملية إعادة تموضع الشفة من العمليات الجراحية الشائعة في تدبير الابتسامة اللثوية. تهدف هذه الدراسة الى تقييم تأثير مدة ترك الخياطة على فعالية عملية إعادة تموضع الشفة التقليدية كعمل جراحي تجميلي في تدبير الابتسامة اللثوية الناجمة عن فرط حركة الشفة العلوية من حيث كمية التغطية اللثوية مع مرور الزمن ومنع النكس اللاحق. تتألف عينة البحث من 10 مرضى اناث راجعوا كلية طب الأسنان بشكوى ظهور زائد للثة عند الابتسام حيث تم اجراء عملية إعادة تموضع الشفة التقليدية لجميع مرضى العينة وتركت الخياطة لمدة 14 يوم عند نصف المرضى و21 يوم عند المرضى الخمسة الأخرين. وتضمنت المراقبة السريرية أخذ الصور الأمامية والجانبية للمرضى قبل المعالجة وبعد شهر و3 أشهر و6 أشهر. أظهرت نتائج هذه الدراسة أن ترك الخياطة لأسبوع أضافي لا يملك أي أثر جوهري في ثبات النتائج وأن المدة المفضلة لترك الخياطة وفق ظروف هذه الدراسة هي اسبوعبن (14 يوم). Lip Reposition is considered one of the common surgical procedures in management of the gummy smile. This study aims to evaluate the effect of suturing period on the efficiency of Lip Reposition as a plastic surgery in management of the gummy smile caused by hyperactive upper lip on the gingival coverage by time and recurrence. The study sample consists of 10 female patients who came to the faculty of dentistry with a major complain of an excessive gingival display while smiling. Lip reposition was done for the whole sample and the suturing were kept for 14 days in half of the sample and for 21 days in the other 5 patients. Follow up includes taking face and profile pictures before and after 1, 3 and 6 months after the surgery. The result showed that keeping the sutures for an extra week has no effect on the stability of the cosmetic results and the preferred period to keep the sutures within the conditions of this study is 14 days.